Thermo-Structural Behaviour Prediction of the Nose Cap of a Hypersonic Vehicle Based on Multifield Coupling - Xuewen Sun; Haibo Yang; Tao Mi (International Journal of Aerospace Engineering)
The analysis of thermo-structural behaviour is crucial to the nose cap of a hypersonic vehicle under aerothermodynamic loads. Considering chemical nonequilibrium of the flow field, heat transfer, and deformation of the structure, a fluid-thermal-structural coupling model of the typical nose cap was established. The coupling relation between the flow field and nose cap was analyzed. The results show that the fluid-thermal-structural model can effectively predict the response of the nose cap under a hypersonic environment. The highest temperature and the peak of maximum principal stress appear at the front of the nose cap at an initial stage. As time goes on, the highest temperature increases gradually and the peak of maximum principal stress decreases after reaching a certain value. The position of the peak of maximum principal stress gradually moves to the inside of the nose cap and eventually stabilizes. With the increase in the Mach number, the highest temperature and the peak of maximum principal stress of the nose cap increase. The fluid-thermal-structural coupling model can provide guidance for the optimal design of the nose cap of a hypersonic vehicle.